The Influence of Online Customer Reviews and Ratings on Purchasing Decisions Through Consumer Trust as A Mediation Variable: Study of Camilan Khanza Consumers in Malang - Khanza Farid Bahtiar; Fani Firmansyah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2024)
This research examines the impact of online customer reviews and ratings on purchasing decisions, with consumer trust as a mediating variable among customers of the Camilan Khanza online store in the Malang Raya region. This research utilizes a quantitative methodology with a descriptive framework. The research population comprises consumers from the Camilan Khanza online store in Malang Raya, encompassing the City of Malang, Malang Regency, and Batu City. This study employs purposive sampling, comprising a total sample size of 150 persons from the Malang Raya district. This study used structural equation modeling-partial least squares (SEM-PLS) for data analysis, leveraging SmartPLS software version 3.2.9. The study's findings indicate that 1) online customer reviews have a positive but negligible effect on purchasing decisions, 2) online customer ratings significantly and positively impact purchasing decisions, 3) consumer trust has a significant and positive effect on purchasing decisions, 4) online customer reviews significantly and positively influence consumer trust, 5) online customer ratings significantly and positively affect consumer trust, 6) online customer reviews indirectly influence purchasing decisions through consumer trust, and 7) online customer ratings indirectly affect purchasing decisions via consumer trust.